Uniform Crime Reporting Program Data (United States): Detailed Arrest and Offense Data for 321 Counties, 1988 ([Verlag nicht ermittelbar], 1991)
The files in this collection contain counts of arrests and offenses for Part I and Part II offenses: murder, rape, robbery, assault, burglary, larceny, auto theft, arson, forgery, fraud, embezzlement, vandalism, weapons violations, sex offenses, drug and alcohol abuse violations, gambling, vagrancy, curfew violations, and runaways. County populations are also reported. Data are included for 321 counties in the United States.